2015
DOI: 10.1099/mgen.0.000042
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and establishment of fluoroquinolone-resistant Shigella sonnei into Bhutan

Abstract: Shigella sonnei is a major contributor to the global burden of diarrhoeal disease, generally associated with dysenteric diarrhoea in developed countries but also emerging in developing countries. The reason for the recent success of S. sonnei is unknown, but is likely catalysed by its ability to acquire resistance against multiple antimicrobials. Between 2011 and 2013, S. sonnei exhibiting resistance to fluoroquinolones, the first-line treatment recommended for shigellosis, emerged in Bhutan. Aiming to reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(60 reference statements)
3
9
0
Order By: Relevance
“…IncI and IncB/O plasmids belong to the IncI-complex (IncI, IncB/O, IncK, IncZ), which have comparable antisense RNA plasmid replication control mechanisms 69 . Our results concur with previous reports that proposed a commonality of IncI-complex plasmids associated with the bla CTX-M element in S. sonnei from countries at various stages of economic development 21,47,7074 . The reasons for these specific plasmid-host combinations remain elusive; however, we found that IncI and IncB/O plasmids displayed the highest in vitro conjugation efficiencies compared to other ESBL-encoding plasmids.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…IncI and IncB/O plasmids belong to the IncI-complex (IncI, IncB/O, IncK, IncZ), which have comparable antisense RNA plasmid replication control mechanisms 69 . Our results concur with previous reports that proposed a commonality of IncI-complex plasmids associated with the bla CTX-M element in S. sonnei from countries at various stages of economic development 21,47,7074 . The reasons for these specific plasmid-host combinations remain elusive; however, we found that IncI and IncB/O plasmids displayed the highest in vitro conjugation efficiencies compared to other ESBL-encoding plasmids.…”
Section: Discussionsupporting
confidence: 93%
“…To date, cipR S. sonnei has been reported in children across Asia 16,17 , as well as homeless individuals and men-who-have-sex-with-men (MSM) in Canada, the US, Taiwan, and the UK 14,1820 . Of further concern is the observation that cipR S. sonnei have the ability to acquire resistance to second-line alternative drugs such as ceftriaxone 21 , which further limits alternative treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of CA S. sonnei isolates were compared with the genomes of global S. sonnei clones reported by previous studies (see Data Set S1, sheet 2, in the supplemental material) (1921) using genome-wide SNP analysis. The isolates from the aforementioned studies (188 total) were selected based on following criteria: (i) to represent all lineages as per Holt et al (19), (ii) different clades described by authors (Global III, Central Asia III), and (iii) various ciprofloxacin resistance mutations.…”
Section: Resultsmentioning
confidence: 99%
“…sonnei 7 , 8 , 15 , 17 . In addition to these horizontally-acquired AMR determinants, chromosomal mutations in the Quinolone Resistance Determining Region (QRDR) (that confer resistance to ciprofloxacin, the recommended treatment for shigellosis) 18 have also been reported in shigellae isolated from Asia, Latin America, and high-income nations 7 , 11 , 14 , 19 . Ciprofloxacin-resistant Shigella were recently recognised by the World Health Organisation as one of the top dozen agents for which new antimicrobials are urgently needed.…”
Section: Introductionmentioning
confidence: 99%